Aktivitas Antibakteri Gel Lidah Buaya Terhadap Staphylococcus aureus - Resmila Dewi; Erda Marniza (Fakultas Pertanian, Universitas Timor, 2019)
Aloe vera is a functional plant because can be used to treat various diseases, including skin diseases by Staphylococcus aureus infection, which causes inflammation of the skin, ulcers, acne, and so on. This research aimed to determine the inhibited effect of Aloe vera gel to the growth of Staphylococcus aureus and the most effective concentration for the resistance against both of bacteria tested. Antibacterial activity of Aloe vera gel was tested using well diffusion method on Mueller Hinton Agar (MHA) at different concentrations 30; 40; 50; 60; 70%. Observation was conducted after incubation for 48 hours at room temperature. The results showed that Aloe vera gel inhibition the growth of S. aureus, it was indicated by the formation of inhibition zones. The most effective of Aloe vera gel inhibiting the growth of S. aureus at 70% with the size 12,81 mm. This shows that the higher the concentration of aloe vera gel is given, the greater the diameter of the inhibition zone.